ANALISIS KUALITAS WEBSITE PORTAL UNIVERSITAS AHMAD DAHLAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Meli, Khofipa Melianti; Supriyanto (STMIK Palangkaraya, 2022)
Web-based information systems in universities are currently shown as a medium for delivering academic information. One of them is a website as a reference for students to get accurate and up to date. Assessment of the quality of the website can be seen from the expectations of its users, Importance Performance Analysis (IPA) is used as a method to measure the quality of a website as an analytical tool in the form of level of conformity analysis, gap analysis, and quadrants. The results of the analysis of the calculation of the average value of the gap on website Ahmad Dahlan University PORTAL negative (<0) in the amount of -0.54. These results indicate that the level of performance and quality of the website is still lacking and has not met user expectations. Overall, users of the website were dissatisfied with the quality of the website. The results of the quadrant analysis showed that there were 6 attributes entered in Quadrant 1.5, attributes entered in Quadrant 2, 4 attributes entered in Quadrant 3, and 6 attributes entered in Quadrant 4.